Evaluation of the Effectiveness of the Implementation of Sharia Principles in Multi-Purpose Financing Products ( PMG ) for State Civil Apparatus ( ASN ) at Bank Sumut Syariah - Zuhrani Gumas Damanik; Tri Inda Fadhila Rahma; Nur Ahmadi Bi Rahmani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study evaluates the effectiveness of Islamic-principle implementation in the Multi-Purpose Financing (PMG) product at Bank Sumut Syariah’s Marelan Raya sub-branch, focusing on Civil Servant (ASN) customers. Employing a qualitative case-study approach, data were gathered through in-depth interviews with the branch head, analysis of internal policy documents, and a customer-satisfaction survey. Findings reveal that the murabahah contract, strictly supervised by the Sharia Supervisory Board and supported by internal audits and structured risk governance, achieves full compliance with the prohibitions of riba, gharar, and maysir; this is reflected in a low Non-Performing Financing (NPF) rate (≈1.8 %) and high customer satisfaction (75 % satisfied, 20 % moderately satisfied). Nevertheless, limited Islamic-finance literacy, perceptions of administrative bureaucracy, and competition from conventional products remain significant challenges. Intensive education, process digitalization, and competitive feature innovation are recommended to boost market penetration and strengthen customer trust. The findings affirm that Bank Sumut’s sharia PMG not only complies with Islamic principles but also delivers economic benefits and a sense of justice to the ASN segment.